Endoscopic ultrasound-guided transvascular needle biopsy of thoracic and abdominal lesions: a multicenter experience - Garcia-Sumalla, Albert; Subtil, Jose C.; de la Serna, Carlos; Maisterra, Sandra; Aparicio, Jose Ramon; Bojorquez, Alejandro Enrique; Montañes, Rafael Leon; Vazquez-Sequeiros, Enrique; Gornals, Joan B. (Endoscopy International Open, 2020)
Background and study aims Traditionally in the case of a vascular interposition, endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) has been contraindicated. A transvascular route (TV) is feasible and probably a safe alternative approach in selected patients, but data are scarce. The primary aim of this study was to analyze the diagnostic yield and safety of EUS-TV-FNA in thoracic and abdominal lesions. Secondary aims included evaluation of the clinical impact and technical aspects.Patients and methods A retrospective multicenter study was conducted with inclusion of all consecutive patients that underwent EUS-TV-FNA from July 2007 to January 2020. Feasibility, cytopathology, procedure details, and safety were evaluated. Univariate analysis was performed to identify variables associated with incidents, cytopathological diagnosis, and clinical impact.Results Data were collected from a total of 49 cases and 50 EUS-TV-FNAs. The aorta (n = 19) and portal system (n = 17) were the most frequently punctured. The most frequent lesions were mediastinal lymph nodes (n = 13) and pancreatic tumors (n = 11). The diagnostic yield was 86 %, and there were nondiagnostic samples in seven cases. Overall sensitivity, specificity, and accuracy were 88 % (95 %CI,0.74–0.96), 100 % (95 %CI,0.59–1), and 90 % (95 %CI,0.78–0.96), respectively. Only three incidents were detected: two mural hematomas and a self-limited bleeding of gastroduodenal artery. In most patients, there was a significant impact on clinical management (88 %). Arterial vessel and ASA-III had a trend with incidents (both, P < 0.08). Rapid on-site evlauation was found to be an independent predictor for obtaining a conclusive sample (OR 6.2; 95 %CI, 1.06–36.73, P < 0.04).Conclusions EUS-TV-FNA is feasible, seems to be safe, and can be recommended when no other targets are available, and the information obtained would impact on the clinical plan.